Loss of all ndh genes as determined by sequencing the entire chloroplast genome of the black pine Pinus thunbergii. - Wakasugi, T (1994)
The complete nucleotide sequence (119,707 bp) of the black pine (Pinus thunbergii) chloroplast genome has been determined. It contains 4 rRNA genes and 32 tRNA genes. To our knowledge, the tRNAPro (GGG) gene has not been found in any other chloroplast genome analyzed. Sixty-one genes encoding proteins and 11 conserved open reading frames are also found. Extensive rearrangements are apparent in the chloroplast genome relative to those of other land plants. The most striking feature is the loss of all 11 functional genes (ndh genes) for subunits of a putative NADH dehydrogenase that are found in the chloroplast genomes of angiosperms and a bryophyte. Four ndh genes were completely lost and the other 7 genes remain as obvious pseudogenes. This unexpected finding raises the possibility that all ndh genes have been transferred to the nucleus or that an NADH dehydrogenase is not essential in black pine chloroplasts.